Alternative Representation of Management Control Design: an empirical exploration and critical analysis - Jim Rooney (Australasian Accounting, Business and Finance Journal, 2013)
This paper describes a critical analysis of three recently published theoretical frameworks developed to explain management control design within inter-organisational collaborations. The particular concern is that, despite a plethora of theoretical frameworks attempting to explain management control design choices, these frameworks have yet to be utilised in practice. The focus is on their respective ability to explain control change in response to coordination problems, recognising the interactive nature of inter-organisational relationships. It adopts an approach previously used in the accounting literature for the purpose of promoting discussion and critical reflection. The resulting case study analysis provides critical insight on how each of the frameworks can influence discipline-specific understanding of control evolution. Improved understanding is expected to indicate potential usefulness to accounting practice. Hence, within inherent limitations, the paper reflects on opportunities to consolidate extant management accounting theory.
Keywords: Management Control; Outsourcing; Coordination; Critical Reflection